Kirk-Othmer Encyclopedia of Chemical Technology 2011
DOI: 10.1002/0471238961.opialedn.a01
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Analgesics

Abstract: Opiate analgesics comprise a large group of organic compounds that act on the level of the the brain. The propensity for abuse and developing dependence on drugs has led to the search for analogues free of those perils. Compounds that act as central analgesivs range all the way from congeners with complex chemical strutures derived from morphine and thebain to relatively simple organic compounds. This article ilustrates the various classes of central as well as their biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…[24] The distinctive position of codeine (22) in the modern medicine continues to stimulate endeavors to an understanding of its euphoria and also analgesic properties. [25] White et al in 1999 reported a methodology for the formation of codeine by using the intramolecular insertion reaction of a carbenoid into a benzylic methine CH bond for the construction of the C13 quaternary center and also the pentacyclic framework of the alkaloid. The total synthesis of codeine (22) was commenced from isovanillin 16 that after several steps afforded keto ester 17.…”
Section: Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] The distinctive position of codeine (22) in the modern medicine continues to stimulate endeavors to an understanding of its euphoria and also analgesic properties. [25] White et al in 1999 reported a methodology for the formation of codeine by using the intramolecular insertion reaction of a carbenoid into a benzylic methine CH bond for the construction of the C13 quaternary center and also the pentacyclic framework of the alkaloid. The total synthesis of codeine (22) was commenced from isovanillin 16 that after several steps afforded keto ester 17.…”
Section: Alkaloidsmentioning
confidence: 99%
“…For the first time, codeine was identified by Pierre Jean Robiquet in 1832, [23] which it is known naturally in the sap of the opium poppy, Papaver somniferum [24] . The distinctive position of codeine ( 22 ) in the modern medicine continues to stimulate endeavors to an understanding of its euphoria and also analgesic properties [25] . White et al .…”
Section: Applications Of Robinson Annulation In the Total Synthesis O...mentioning
confidence: 99%